The Weak 3D Topological Insulator Bi12Rh3Sn3I9 - Le Anh, Mai; Kaiser, Martin; Ghimire, Madhav Prasad; Richter, Manuel; Koepernik, Klaus; Gruschwitz, Markus; Tegenkamp, Christoph; Doert, Thomas; Ruck, Michael (Chemistry - A European Journal, 2020)
Topological insulators (TIs) gained high interest due to their protected electronic surface states that allow dissipation-free electron and information transport. In consequence, TIs are recommended as materials for spintronics and quantum computing. Yet, the number of well-characterized TIs is rather limited. To contribute to this field of research, we focused on new bismuth-based subiodides and recently succeeded in synthesizing a new compound Bi12Rh3Sn3I9, which is structurally closely related to Bi14Rh3I9 – a stable, layered material. In fact, Bi14Rh3I9 is the first experimentally supported weak 3D TI. Both structures are composed of well-defined intermetallic layers of ∞2[(Bi4Rh)3I]2+ with topologically protected electronic edge-states. The fundamental difference between Bi14Rh3I9 and Bi12Rh3Sn3I9 lies in the composition and the arrangement of the anionic spacer. While the intermetallic 2D TI layers in Bi14Rh3I9 are isolated by ∞1[Bi2I8]2− chains, the isoelectronic substitution of bismuth(III) with tin(II) leads to ∞2[Sn3I8]2− layers as anionic spacers. First transport experiments support the 2D character of this material class and revealed metallic conductivity.
CRIS-Team Scopus Importer:2022-04-14
Keywords: crystal growth; crystal structure; topological band gap; topological insulators; weak topological insulators